Where are the turtles when they are not? : Underwater refuges used by Hydromedusa tectifera COPE, 1869 in a suburban stream - Semeñiuk, María Belén (2020)
Habitat requirements of Hydromedusa tectifera from an urban impacted stream from the Buenos Aires province, the Rodriguez stream, are here studied. We describe the type of underwater refuges, how they are used in different stream sections, stream margins, year season, size class and sex of the individuals, and analyze patterns of recurrence and aggregative use of refuges. Fieldwork was carried out from March 2017 to January 2018. Turtles were caught manually recording the following variables: site, transect and margin, sex, straight carapace length, and weight. Substrate types are differently used according to stream section, stream margin, year season and size class of individuals, but no difference was found between sexes. In the whole stream, most used refuges were the hollows on the margins (55.05%), followed by marginal aquatic vegetation (19.27%). Turtles of all class sizes and both sexes refuge into hollows on the stream margins. Despite different microhabitats provide refuge to turtles during all year seasons, hollows are the most important refuge during extreme cold and extreme hot seasons. In addition, turtle recaptures evidence a recurrence and aggregative pattern in the use of refuges. This information provides insight into the key aspects of the microhabitat requirements of the species and will be certainly useful in mitigating and preventing negative effects of the current stream management policies. It is worth highlighting the need to keep the stream margins unaltered to favor the presence of turtles in urban environments.